Micromineral status of soil, fodders and cattle from Idukki and Ernakulam districts of Kerala state, India and their interrelation - G. DEVI; M. C. SHARMA; U. DIMRI; P. SHEKHAR and P. M. DEEPA (International Journal of Advanced Research, 2014)
Minerals are inorganic dietary constituents required for various metabolic processes in the body. Availability of minerals to animals in appropriate quantities is a major factor determining the health and productivity. Keeping it in view, a baseline survey was conducted in different blocks of Idukki (Idukki, Thodupuzha and Elamdesom) and Ernakulam (Vazhakulam and Muvattupuzha) districts of Kerala state. The aim of the study was to assess the major micro-minerals i.e., copper (Cu), Zinc (Zn) and Iron (Fe) status of soil, plant/fodder and cattle in two districts of Kerala. Soil (n=150), Fodder (n=150) and Serum (n=160) samples from cattle were collected from two districts of Kerala. Minerals in soil, plant/fodder (composite) and serum were estimated by AAS (Atomic Absorption Spectrophotometry). The average Cu, Zn and Fe contents of soil in two representative districts of Kerala were found to be 1.47±0.11, 1.81±0.11 and 37.59±1.0 μg/gm, respectively. The percent of soil deficient in Cu, Zn and Fe were 31.7%, 34.2% and 0%, respectively. Similarly, the average Cu, Zn and Fe contents of fodder were 9.29±0.21, 41.16±1.8 and 710.70±14.48 μg/gm with deficiency of 38.66%, 38% and 0%, respectively. The overall prevalence of Cu, Zn and Fe deficiency in serum samples of cattle were 46.87%, 40.00% and 15%, respectively and in the two representative districts of Kerala. Significant correlation was observed at 1% and 5% level for Cu, Zn and Fe concentrations in soil-fodder-bovine serum in almost all districts